Tentacle patterning during Exaiptasia diaphana pedal lacerate development differs between symbiotic and aposymbiotic animals - Presnell,Jason S.; Wirsching,Elizabeth; Weis,Virginia M. (PeerJ, 2022)
Exaiptasia diaphana, a tropical sea anemone known as Aiptasia, is a tractable model system for studying the cellular, physiological, and ecological characteristics of cnidarian-dinoflagellate symbiosis. Aiptasia is widely used as a proxy for coral-algal symbiosis, since both Aiptasia and corals form a symbiosis with members of the family Symbiodiniaceae. Laboratory strains of Aiptasia can be maintained in both the symbiotic (Sym) and aposymbiotic (Apo, without algae) states. Apo Aiptasia allow for the study of the influence of symbiosis on different biological processes and how different environmental conditions impact symbiosis. A key feature of Aiptasia is the ease of propagating both Sym and Apo individuals in the laboratory through a process called pedal laceration. In this form of asexual reproduction, small pieces of tissue rip away from the pedal disc of a polyp, then these lacerates eventually develop tentacles and grow into new polyps. While pedal laceration has been described in the past, details of how tentacles are formed or how symbiotic and nutritional state influence this process are lacking. Here we describe the stages of development in both Sym and Apo pedal lacerates. Our results show that Apo lacerates develop tentacles earlier than Sym lacerates, while over the course of 20 days, Sym lacerates end up with a greater number of tentacles. We describe both tentacle and mesentery patterning during lacerate development and show that they form through a single pattern in early stages regardless of symbiotic state. In later stages of development, Apo lacerate tentacles and mesenteries progress through a single pattern, while variable patterns were observed in Sym lacerates. We discuss how Aiptasia lacerate mesentery and tentacle patterning differs from oral disc regeneration and how these patterning events compare to postembryonic development in Nematostella vectensis, another widely-used sea anemone model. In addition, we demonstrate that Apo lacerates supplemented with a putative nutrient source developed an intermediate number of tentacles between un-fed Apo and Sym lacerates. Based on these observations, we hypothesize that pedal lacerates progress through two different, putatively nutrient-dependent phases of development. In the early phase, the lacerate, regardless of symbiotic state, preferentially uses or relies on nutrients carried over from the adult polyp. These resources are sufficient for lacerates to develop into a functional polyp. In the late phase of development, continued growth and tentacle formation is supported by nutrients obtained from either symbionts and/or the environment through heterotrophic feeding. Finally, we advocate for the implementation of pedal lacerates as an additional resource in the Aiptasia model system toolkit for studies of cnidarian-dinoflagellate symbiosis.
Keywords: Symbiosis; Aiptasia; Sea anemone; Laceration; Asexual reproduction; Cnidaria; Anthozoa; Hexacorallia; Breviolum; Symbiodiniaceae